110 Laparoscopic paraortic lymphdenectomy by anatomical highlighted landmarks. (18th September 2019) - Fernandes, R; Alexandre, SES; Anton, C; Mancusi Carvalho, JP; Araújo, M; Dias Genta, ML; Sampaio, D; Miglino, G; Dias, A; Sadalla, JC; Carvalho, JP
Abstract : Objectives: To demonstrate a laparoscopic stepwise approach to a paraortic lymphdenectomy based on anatomical landmarks. Methods and interventions: Complete endometrial cancer laparoscopic staging including hysterectomy, bilateral salpingooforectomy, omentectomy, pelvic and paraortic lymphdenectomy. Procedure was performed based on classical anatomical landmarks which were highlighted in post video production. Results: Safe stepwise complete endometrial cancer laparoscopic staging including hysterectomy, bilateral salpingooforectomy, omentectomy, pelvic and paraortic lymphdenectomy. Procedure was performed based on classical anatomical landmarks which were highlighted in post video production. Conclusions: Laparoscopic paraortic lymphdenectomy is a complex procedure fraught with dangers. A stepwise approach allows for a clean, secure and complete procedure with diminished risks for the patient. We believe that a stepwise approach associated to highlighted landmarks improve teaching and education in surgical procedures.